Effects of Metformin-Single Therapy on the Level of Inflammatory Markers in Serum of Non-Obese T2DM Patients with NAFLD - Mitrovic, Bojan; Gluvic, Zoran; Macut, Djuro; Obradovic, Milan; Sudar-Milovanovic, Emina; Soskic, Sanja; Stajic, Dragan; Isenovic, Esma R. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background and Objectives: Non-alcoholic fatty liver disease (NAFLD) is associated with inflammation and subsequent increase in cardiovascular risk. Because of its widespread presence and distribution, invasive diagnostic procedures (i.e., liver biopsy) are reserved for a limited number of subjects. With liver ultrasound, Fatty liver index (FLI) and fibrosis-4 (FIB-4) scores non-invasively assess liver steatosis and fibrosis. We aimed to evaluate the changes in inflammatory markers and FLI/FIB-4 scores in non-obese metformin-treated type 2 diabetes patients (T2DM) with NAFLD. Methods: All subjects underwent abdominal ultrasound aiming for NAFLD stratification (grade 1 to 3 according to its severity). Metabolic parameters (morning glycaemia, HbA1C, lipids, liver function tests), serum inflammatory markers (C-reactive protein, ferritin, and nitric oxide) and FLI/- FIB-4 were calculated. Results: FLI score and ultrasound NAFLD grades were found to correlate (p<0.05). We observed a significant correlation between the levels of ferritin and C-reactive protein (CRP) (p<0.05), and the FLI (p<0.05). Body weight (BW) (p<0.05), waist circumference (WC) (p<0.05), the levels of HbA1c (p<0.05), transferrin (p<0.05), insulin (p<0.05), and FLI score (p<0.05) significantly differed between groups as defined by the severity of NAFLD. Conclusion: This pilot study suggests that the serum inflammatory markers at the average normal values point to the sufficiency of metformin-single therapy in inflammation control in non-obese T2DM patients with NAFLD.
Keywords: Diabetes